2006
DOI: 10.1107/s160053680601991x
|View full text |Cite
|
Sign up to set email alerts
|

(E)-N′-(3-Chlorobenzylidene)isonicotinohydrazide

Abstract: The molecule of the title compound, C13H9ClN3O, is roughly planar and displays a trans configuration with respect to the C=N double bond. The dihedral angle between the benzene and pyridine rings is 4.8 (3)°. The crystal structure is stabilized by intermolecular N—H...N hydrogen bonds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 0 publications
3
10
0
Order By: Relevance
“…The bond lengths and bond angles in the title compound ( Fig. 1) are within normal ranges (Allen et al, 1987) and comprable with those observed in similar compounds (Qiu et al, 2006;Yang & Guo, 2006;Yang, 2006). The dihedral angle between the C1-C10 naphthyl ring and C14-C19 benzene ring is 70.1 (2)°.…”
Section: S1 Commentsupporting
confidence: 80%
“…The bond lengths and bond angles in the title compound ( Fig. 1) are within normal ranges (Allen et al, 1987) and comprable with those observed in similar compounds (Qiu et al, 2006;Yang & Guo, 2006;Yang, 2006). The dihedral angle between the C1-C10 naphthyl ring and C14-C19 benzene ring is 70.1 (2)°.…”
Section: S1 Commentsupporting
confidence: 80%
“…Recently, we have reported a few hydrazone compounds [4][5][6]. The title crystal structure consists of a Schiff base molecule and a methanol molecule.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we have reported af ew hydrazone compounds [4][5][6]. The title crystal structure consists of aSchiff base molecule and a methanol molecule.…”
Section: Discussionmentioning
confidence: 99%